Efficacy and prognostic analysis of bronchoscopic intervention in elderly patients with tracheobronchial tuberculosis - Tian, Yueyang; Su, Tianhe; Shen, Leilei; Zhou, Jikun; Sun, Yang (Frontiers in Medicine, 2026)
This study investigated the efficacy and prognosis of bronchoscopic interventional therapy in elderly patients with tracheobronchial tuberculosis (TBTB). We prospectively included 142 elderly patients with TBTB for interventional treatments such as bronchoscopic balloon dilation, mechanical evacuation, and stent implantation, and long-term follow-up (median 28.4 months). The results showed that the technical success rate of interventional therapy was 90.8, 92.3% of patients had improved symptoms, and FEV1 was significantly improved from 43.2% at baseline to 65.8% after surgery (p < 0.001). Fibrostenosis TBTB (OR 3.42), Freitag grade 5 stenosis (OR 2.76), stenosis length > 2 cm (OR 2.18), and Charlson comorbidity index ≥3 (OR 1.98) were independent predictors of poor prognosis. Restenosis occurred in 27.1% of patients after surgery, and the survival rate of older patients (≥75 years) was significantly lower than that of younger patients (81.6% vs. 94.2%, p = 0.003). In this study, we propose a prognostic risk scoring model and confirm that bronchoscopic intervention is safe and effective in elderly patients with TBTB, but patient selection is crucial.